2013
DOI: 10.1155/2013/529187
|View full text |Cite
|
Sign up to set email alerts
|

18-Fluorodeoxyglucose Uptake by Positron Emission Tomography in Extraocular Muscles of Patients with and without Graves' Ophthalmology

Abstract: Objective. To compare 18-fluorodeoxyglucose (FDG) uptake by positron emission tomography (PET) in extraocular muscles (EOMs) of patients with Graves' ophthalmopathy (GO) versus patients without GO. Design. Prospective, observational, comparative, and cross-sectional study. Participants. Thirty-two eyes of patients with GO and seventy eyes of patients without GO. Methods. We prospectively included patients older than 18 years of age with and without GO. FDG-PET imaging study was performed; standardized unit val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…This suggests that 18-FDG may detect those cases in which clinical assessment is confusing and VISA is not precise. As previously published by our group [20], patients with GO do have increased FDG uptake compared with patients without GO.…”
Section: Discussionsupporting
confidence: 78%
“…This suggests that 18-FDG may detect those cases in which clinical assessment is confusing and VISA is not precise. As previously published by our group [20], patients with GO do have increased FDG uptake compared with patients without GO.…”
Section: Discussionsupporting
confidence: 78%
“…Biopsy of the orbital tissue may be useful to differentiate EGO from other inflammatory or infiltrating diseases, but the diagnosis of EGO can often be made on clinical and radiological grounds alone. 18-Fluorodeoxyglucose positron emission tomography scans have been used in some series in the diagnosis of cases where clinical doubt exists ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of its main advantages over other methods is its ability to detect early inflammatory stages prior to structural changes in the tissue [88]. Recently, García-Rojas et al demonstrated in PET combined with CT (PET/CT) imaging a significant correlation between extraocular muscle uptake of 18-fluorodeoxyglucose (18-FDG) radiotracer and GO developed in hyperthyroid patients [89]. These studies indicate that modern PET/CT imaging modality may provide the valuable clinical information and may be a helpful tool in detecting, localizing, and quantifying the GO inflammation.…”
Section: Radionuclide-based Imaging Evaluation Of Graves' Ophthalmopathymentioning
confidence: 99%
“…Lately, the high-resolution PET/CT have been introduced to clinical practice for improved detection, disease grading, and follow-up of patients with GO in order to optimize the treatment in the inflammatory GO phase. Several novel radiotracers have been employed in PET/CT imaging, including gallium-68 and fluor-18 to supply valuable information on localizing and quantifying of GO-related inflammation in retrobulbar tissues [89][90]. Importantly, the availability of novel PET tracers for high-resolution and hybrid imaging in PET/CT enables to evaluate selectively the actual status of immune activity in any single extraorbital muscle.…”
Section: Predicting Therapeutic Efficacy and Disease Activity Based Omentioning
confidence: 99%